ANALISIS PENENTUAN PENDAPATAN LABA PADA USAHA DAUR ULANG LIMBAH AN-ORGANIK PADA BANK SAMPAH - Lindawati Lindawati; Anggun Angraini; Indawati Indawati; Wulandari Cahyani Putri (S1 Accounting Program, Universitas Pamulang, 2019)
The purpose of Community Service Activities is to carry out one of the Tri Darma of Higher Education. In addition, it is expected that through community service, the existence of higher education institutions can make a major contribution to the development and application of knowledge to the community. The method used in this Community Service is expository namely the delivery of material verbally and inquiry that is learning that emphasizes the process of critical and analytical thinking related to accounting and marketing management with a deep understanding of the material on how to determine the future. The results of community service obtained are increased knowledge for members and leaders of the Griya Asri Pamulang Garbage Bank, especially in terms of calculating the value of income starting from calculating the cost of production up to the cost of the product, in addition to utilizing the waste, it is expected that they will be more can change the community paradigm to interpret waste as something that has value to be reused while reducing the amount of national waste. At the garbage bank, organic waste will be recycled into compost. While non-organic waste will be reprocessed so that it can be economically useful. The construction of a garbage bank can also be a momentum to foster community collective awareness to start sorting, recycling, and utilizing waste, because waste has a fairly good sale value.Keywords: Porfit Revenue; Recycle